Recent Approaches for Wound Treatment - Pagano, Cinzia; Viseras, César; Perioli, Luana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this Special Issue is to describe the recent approaches for and efficacious treatment of wounds from different aspects. These include the description of new ingredients (e.g. A.P.I., polymers) able to stimulate the wound healing, new delivery systems, new formulations as well as new understanding in the stimulation of physiological biochemical pathways (that change according to many factors such as age, sex, etc.) involved in wound healing.